Our Amazing Animal Friends - Stuart, Gene. S.; Nang Chan Yeema (United States of America Library of Congress CP Data, 1990)
Introduces record holders of the animal world, including the largest lizard and the fastest mammal.
Keywords: Juvenile Nonfiction